Synergistic enhancement of coalbed methane hydration process by magnetic field and NiMnGa micro-nano fluid - Wu, Qiong; Lin, Nengyu; Li, Li; Chen, Feng; Xv, Xianfu; Zhang, Baoyong; Wu, Qiang; Liu, Chuanhai (Frontiers in Energy Research, 2022)
Coalbed methane is an important renewable energy source. Gas hydration technology is a new method for enhancing the utilization of coalbed methane and reducing environmental pollution. Long induction periods, sluggish formation rates, low hydrate yields, and difficulty removing heat during hydrate formation are all issues with gas hydration technology. In this paper, 3 wt% NiMnGa (NMG) phase-change micro/nanoparticles and 0.05% sodium dodecyl sulphate (SDS) were compounded, and gas hydration experiments were conducted under various initial pressures and gas sample conditions to investigate. The findings revealed that NMG has efficient mass transfer properties as well as phase-change heat absorption properties, which significantly improved the kinetic process of the gas hydrate by mass and heat transfer, shortened the induction time, increased gas consumption, and increased the gas consumption rate during the rapid hydrate growth period. When the initial pressure was 6.2 MPa, the induction time was reduced by 89.26%, 92.48%, and 95.64%, and the maximum gas consumption rate was increased by 238.18%, 175.55%, and 113.60%, respectively, when using different concentrations of methane in the NMG-SDS system compared to the pure SDS system. The NMG used in this paper showed potential for future use in mixed gas hydration technology.